The Effect of the Articulation Learning Model on Students’ Mathematics Achievement - Nasrul Bayumi; Dodik Mulyono; Anna Fauziah (Jurnal Inovasi Matematika, 2025)
This study analyzes the influence of the Articulation Learning Model on students’ mathematics learning. The research employed a quasi-experimental design using a pretest–posttest control group format, involving 7th-grade students from a private junior high school in Lubuk Linggau. The data were analyzed using a t-test, after confirming that the assumptions of normality and homogeneity were met. The Kolmogorov–Smirnov test yielded p = 0.067 and Levene’s test yielded p = 0.625, both greater than 0.05, indicating that the data were normally distributed and homogeneous. The independent t-test showed a p-value of 0.000 (p < 0.05), indicating a significant difference between the experimental and control groups. The mean score of the experimental group was 87, while that of the control group was 66. These results demonstrate that the use of the Articulation Learning Model had a strong positive effect on students’ mathematics learning outcomes, particularly in the topic of statistics.